Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5213/inj.2012.16.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lower Urinary Tract Symptoms and Depression on Health-Related Quality of Life in Older Adults

Abstract: PurposeWe aimed primarily to investigate the level of health-related quality of life (HRQoL), lower urinary tract symptoms (LUTS), and depression in older adults and secondly to identify the impact of LUTS and depression on HRQoL.MethodsA community-based cross-sectional study was conducted from April to November 2010. Participants were recruited from five community senior centers serving community dwelling older adults in Jeju city. Data analysis was based on 171 respondents. A structured questionnaire was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…With OAB wet, a person may be unable to stop leakage before reaching the toilet. It has significant effects on health-related QoL in both men and women, affecting their ability to work, physical activity, sexual function, and sleep [141516]. When we treated the female patients with OAB wet, long-term maintenance of antimuscarinic agents should be recommended based on the result from the present study.…”
Section: Discussionmentioning
confidence: 96%
“…With OAB wet, a person may be unable to stop leakage before reaching the toilet. It has significant effects on health-related QoL in both men and women, affecting their ability to work, physical activity, sexual function, and sleep [141516]. When we treated the female patients with OAB wet, long-term maintenance of antimuscarinic agents should be recommended based on the result from the present study.…”
Section: Discussionmentioning
confidence: 96%
“…For example, LUTS patients with comorbid depression had poorer HRQOL than LUTS patients without comorbid depression . A study on Korean males and females with LUTS found that those with more severe depression had poorer HRQOL . Quek found that depressive and anxiety symptoms were factors associated with the HRQOL of patients with LUTS .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that LUTS can negatively impact patients’ health‐related quality of life (HRQoL) . A cross‐sectional survey of 1 627 men aged 40–79 years found 51% of men with BPH reported interference with at least one daily living activity due to urinary dysfunction, compared with 28% of men without BPH .…”
Section: Introductionmentioning
confidence: 99%